The controversial role of CD151 in different solid tumors: promoter or suppressor? - Xue Gao; Sa Liu; Yubo Cao; Lei Shi; Yuanqin Yin (Cancer Cell International)
Abstract As a member of the tetraspanin superfamily, CD151 plays a pivotal role in tumorigenesis, progression, and metastasis. CD151 is involved in various cellular processes, including cell-cell junction, signal transduction, epithelial-mesenchymal transition (EMT), cancer stem cell maintenance (CSCs), angiogenesis, and exosome regulation. Therefore, CD151 is a potential target for tumor therapy and may be valuable in tumor diagnosis and prognosis. Notably, while CD151 predominantly functions as an oncogene in most cancers, it can also exhibit tumor-suppressive roles in specific contexts, indicating that its function is context-dependent. Additionally, CD151 plays a significant role in modulating the immune microenvironment. For instance, CD151 supports the proliferation, activation, and migration of T cells. The CD151 peptide may function as a tumor vaccination by stimulating CD8 + IFNγ + lymphocytes and inducing cytotoxic effects. Thus, the function of CD151 in tumors is intricate and warrants further investigation. In this review, we discuss the diagnostic and prognostic potential of CD151, as well as its regulatory roles in solid cancers, including those of the digestive system, lung, breast, prostate, and gynecological tissues. Basic experiments and clinical data demonstrate the beneficial and detrimental effects of CD151 in malignancies and offer a path forward for future investigation. Graphical abstract Tetraspanins CD151, a transmembrane four superfamily protein, participates in various cellular activities, including cell-cell junction, signal transduction, epithelial-mesenchymal transition, cancer stem cell maintenance, angiogenesis, and exosome regulation. Interestingly, while CD151 primarily acts as a tumor promoter in most cancers, it can also exhibit tumor-suppressive functions in certain contexts. Here, we explore the dual role of CD151 in solid tumors, including those of the digestive tract, lungs, breast, prostate, and gynecological tissue, as well as its diagnostic and prognostic potential.